Kesetaraan Gender dalam Hukum Perkawinan Islam: Antara Idealitas Normatif dan Realitas Sosial - Daulay, Andri Irama; Hakim, Fahmi (Islamic Family Law Department, Sharia Faculty, Stai Syekh Abdur Rauf, Aceh Singkil, 2025)
Gender equality in Islamic marriage law remains a critical and contentious issue, particularly concerning the rights and responsibilities of husbands and wives. Although justice (al-‘adalah) is a fundamental principle in Islam, social and legal practices often reflect disparities, particularly in matters such as divorce rights, financial support (nafkah), and the division of household roles. This study aims to analyze how the implementation of Islamic marriage law in various Muslim countries influences the achievement of gender equality, while also exploring the factors that facilitate or hinder the realization of justice in marriage. This research employs a qualitative study with a normative legal and socio-legal approach. The analysis examines various legal documents, including the Compilation of Islamic Law (Kompilasi Hukum Islam, KHI) in Indonesia, the Islamic Family Law Act in Malaysia, as well as regulations in countries such as Tunisia and Morocco, which have implemented more progressive reforms in marriage law. Additionally, data were gathered through literature reviews and interviews with Islamic legal scholars to understand how interpretations of fiqh and legal texts contribute to shaping fair marital practices. The findings indicate that although several Muslim-majority countries have adopted more egalitarian policies in marriage law, their implementation remains constrained by deeply entrenched patriarchal cultural norms. For instance, while Indonesia and Malaysia have introduced regulations aimed at achieving gender equality, their enforcement is often suboptimal due to the persistence of traditional values that position men as the primary authority figures within households. In contrast, Tunisia and Morocco have successfully enacted more progressive legal reforms, granting women more equitable rights in marriage and divorce. The study concludes that a reinterpretation of Islamic legal texts and fiqh is necessary to ensure that marriage law remains relevant to contemporary social contexts while preserving the fundamental Islamic principle of justice. Legal reforms and increased public awareness regarding the rights and responsibilities of spouses are crucial steps toward establishing a more equitable marital framework. Therefore, collaboration among governments, religious scholars, and society is essential to developing a legal structure that safeguards women's rights in marriage while upholding core Islamic values such as justice, compassion, and human dignity. [Kesetaraan gender dalam hukum perkawinan Islam merupakan isu krusial yang masih menjadi perdebatan, terutama terkait hak dan kewajiban antara suami dan istri. Meskipun prinsip utama dalam Islam adalah keadilan (al-‘adalah), praktik sosial dan hukum yang berlaku sering kali menunjukkan ketimpangan, terutama dalam hal hak talak, nafkah, dan pembagian peran dalam rumah tangga. Penelitian ini bertujuan untuk menganalisis bagaimana implementasi hukum perkawinan Islam dalam berbagai negara Muslim memengaruhi pencapaian kesetaraan gender, serta mengeksplorasi faktor-faktor yang mendukung dan menghambat penerapan keadilan dalam perkawinan. Metode penelitian yang digunakan adalah studi kualitatif dengan pendekatan hukum normatif dan sosio-legal. Analisis dilakukan terhadap berbagai dokumen hukum seperti Kompilasi Hukum Islam (KHI) di Indonesia, Akta Undang-Undang Keluarga Islam di Malaysia, serta regulasi di negara-negara seperti Tunisia dan Maroko yang lebih progresif dalam reformasi hukum perkawinan. Selain itu, data diperoleh melalui kajian literatur dan wawancara dengan pakar hukum Islam untuk memahami bagaimana interpretasi fiqh dan teks hukum berperan dalam membentuk praktik perkawinan yang adil. Hasil penelitian menunjukkan bahwa meskipun regulasi di beberapa negara Muslim telah mengadopsi kebijakan yang lebih setara dalam hukum perkawinan, implementasinya masih terhambat oleh norma budaya patriarkal yang mengakar dalam masyarakat. Indonesia dan Malaysia, misalnya, memiliki regulasi yang berupaya mencapai kesetaraan, tetapi pelaksanaannya sering kali tidak optimal karena pengaruh nilai-nilai tradisional yang masih menempatkan laki-laki sebagai pemegang otoritas utama dalam rumah tangga. Di sisi lain, Tunisia dan Maroko telah berhasil menerapkan reformasi hukum yang lebih progresif, memungkinkan perempuan memiliki hak yang lebih setara dalam pernikahan dan perceraian. Kesimpulan dari penelitian ini menegaskan bahwa reinterpretasi terhadap teks hukum Islam dan fiqh diperlukan agar hukum perkawinan lebih relevan dengan konteks sosial modern tanpa menghilangkan nilai-nilai dasar Islam yang menekankan keadilan. Reformasi hukum serta peningkatan pemahaman masyarakat tentang hak dan kewajiban suami istri menjadi langkah penting dalam mewujudkan perkawinan yang lebih adil. Oleh karena itu, sinergi antara pemerintah, ulama, dan masyarakat diperlukan untuk menciptakan kerangka hukum yang melindungi hak-hak perempuan dalam perkawinan sambil tetap mempertahankan prinsip keadilan dalam ajaran Islam].